Long-acting family planning uptake and associated factors among women in the reproductive age group in East Africa: multilevel analysis - Enyew, Ermias Bekele; Tareke, Abiyu Abadi; Ngusie, Habtamu Setegn; Kasaye, Mulugeta Desalegn; Kebede, Shimels Derso; Feyisa, Mahider Shimelis (Frontiers in Global Women's Health, 2025)
IntroductionThe campaign to encourage sexually active women to utilize family planning is one of the primary initiatives being undertaken globally to reduce unintended pregnancies and fertility rates. Evidence suggests that family planning measures can lower this maternal mortality ratio by nearly 25%. According to our literature search, there is no known study that has reported on the study area to assess utilization and factors associated with the use of long-acting contraceptive methods (LACMs) among women of reproductive age. Therefore, this study aimed to assess long-acting contraceptive method uptake and its associated factors among women of reproductive age in East Africa.MethodsA weighted total of 50,525 women of reproductive age were included in this study. A community-based cross-sectional study was conducted on the most recent Demographic and Health Surveys in 12 East African countries. The pooled prevalence of long-acting contraceptive uptake with a 95% confidence interval (CI) was reported and presented in a forest plot for East African countries using STATA version 14.1. Intraclass correlation coefficient, likelihood ratio (LR) test, median odds ratio, and deviance (−2 log-likelihood) values were used for model comparison and fitness. Adjusted odds ratios (AOR) with a 95% CI and p-value ≤0.05 in the multilevel logistic model were used to declare significant factors associated with long-acting contraceptive uptake.ResultsThe overall prevalence of long-acting contraceptive methods in East African countries was 19.41% (95% CI 19.07%–19.76%). In the multilevel logistic regression analysis, women in the age group of 35–49 years (AOR 1.09, 95% CI 1.06–1.17), women who were married (AOR 1.31, 95% CI 1.10–1.56), and women who were exposed to media (AOR 1.06, 95% CI 1.00–1.13) were significantly associated with LACM uptake. Moreover, living in urban areas (AOR 1.23, 95% CI 1.14–1.32) and living in the highest household wealth index (AOR 1.09, 95% CI 1.01–1.17) were also significantly associated with long-acting contraceptive uptake.ConclusionThe overall utilization of acting contraceptive methods was low. Therefore, future interventions should be planned to target women in younger age groups, with lower socioeconomic backgrounds, and those living in rural areas to improve LACM uptake.